Endoscopy in inflammatory bowel disease: from guidelines to real life. (July 2019) - Negreanu, Lucian; Voiosu, Theodor; State, Monica; Voiosu, Andrei; Bengus, Andreea; Mateescu, Bogdan Radu
Endoscopy has a central role in the management of inflammatory bowel disease (IBD), providing crucial data for diagnostic and therapeutic decisions, treating disease-related complications, and assisting in the early detection of dysplasia and prevention of colorectal cancer in the setting of IBD. Treatment targets have significantly shifted in IBD, focusing on achieving mucosal healing, a more meaningful endpoint than clinical remission. With the emergence of novel therapies, we aim to alter the course of the disease and prevent irreversible damage to the bowel. To that end, obtaining reliable and reproducible assessments of endoscopic disease activity has become an issue of great importance. Although several guidelines include recommendations regarding endoscopic surveillance in patients with long-standing IBD, there is an open debate regarding the best examination method and the appropriate follow-up intervals. Another important issue is whether surveillance guidelines are actually implemented in real-life practice and what is the preferred surveillance method among endoscopists. Significant changes have occurred in the endoscopic world with the development of new diagnostic and therapeutic modalities and their incorporation in everyday practice. We aimed to assess the real-life application of guideline recommendations regarding endoscopy in IBD patients and to review newly emerged data which might impact these recommendations in the near future.